2017
DOI: 10.1016/j.flora.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Ramenta morphology and its variations in Rafflesia (Rafflesiaceae)

Abstract: Ramentae are hair-like structures found on the perigone tube and diaphragm in species of Rafflesia (Rafflesiaceae). Although ramenta morphology provides an important taxonomic character, a consistent terminology has not been used in species descriptions. As such, morphological comparisons among species as well as among populations within a species are difficult. We used a variety of resources to document the morphology including the location and density of ramenta among 18 species of Rafflesia and between popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Our interpretation is matched by the illustration in Mahyuni et al (2015) showing branched ramenta, not toadstool, on the upper part of the perigone tube. Susatya et al (2017) also found compound toadstool ramenta only in the lower part of the diaphragm. As a consequence, we conclude that toadstool ramenta are not found on the upper perigone tube of R. gadutensis (FIG.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Our interpretation is matched by the illustration in Mahyuni et al (2015) showing branched ramenta, not toadstool, on the upper part of the perigone tube. Susatya et al (2017) also found compound toadstool ramenta only in the lower part of the diaphragm. As a consequence, we conclude that toadstool ramenta are not found on the upper perigone tube of R. gadutensis (FIG.…”
Section: Discussionmentioning
confidence: 85%
“…Key differences between R. kemumu and R. gadutensis are color of the perigone lobes; pattern, size, number, and color of warts on the upper surface of the perigone lobes; color and wart presence/absence on the upper surface of the diaphragm; blot arrangement of the two concentric rings of the windows closest to the diaphragm opening; types and distribution of ramenta; number and shapes of processes; and number of anthers (Table 1). Meijer (1984Meijer ( , 1997, Mahyuni et al (2015), and Susatya et al (2017) or obtained from photos by the late Prof.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations